Uwagi o zmianach semantycznych staropolskich rzeczowników osobowych (na podstawie dzieł leksykograficznych) - Piotrowska-Wojaczyk, Agnieszka (Slavia Occidentalis, 2023)
The aim of the presented article is to show semantic changes in Old Polish person-related nouns. Describing selected entries from a diachronic perspective – by comparing semantic notations from the Old Polish Dictionary edited by S. Urbańczyk with definitions from later dictionaries – has allowed me to identify semantic modifications occurring over the centuries (e.g. metaphors, de-metaphorisation, expansion of meaning, pejorative meaning) and to make a number of remarks on the subject.